Characteristics of precipitation and extreme precipitation events over the Drakensberg Mountain range in past and future climates - Takong, Ridick (Department of Environmental and Geographical Science, 2023)
The Drakensberg Mountains is one of the most valuable natural resources in Southern Africa because precipitation over the mountains is the source of rivers that support socio-economic activities in Lesotho, South Africa, and Namibia. Meanwhile, extreme precipitation events over the Drakensberg are a threat to the communities around the mountains. While several studies have shown that mountains are among the most sensitive regions to climate variability and change, the potential impacts of global warming on precipitation and extreme precipitation occurrences over the Drakensberg are poorly understood. This thesis examines the characteristics of precipitation and extreme precipitation events over the Drakensberg in past climate and investigates how the characteristics might change in future climate at various global warming levels under RCP8.5 future climate scenario. Series of climate datasets were analysed for the study. These include observed precipitation datasets from eight satellite products, reanalysis datasets from National Centre for Environmental Prediction (NCEP) Climate Forecast System Reanalysis (CFSR), and climate simulation datasets from the Model for Prediction Across Scales (MPAS), Weather Research and Forecasting Model (WRF), and the National Aeronautics and Space Administration (NASA) Earth Exchange Global Daily Downscaled Projections (NEX), and the Coordinated Regional Climate Downscaling Experiment (CORDEX). All the simulation datasets were evaluated against the observation datasets. Precipitation indices were used to characterize precipitation and extreme precipitation events over the Drakensberg Mountains, with emphasis on widespread extreme events (WEREs). Self-Organizing Map (SOM) technique was employed to group the synoptic patterns over southern Africa, WERE patterns over DMR, and the future climate change projections over the Drakensberg Mountains. Results of this dissertation reveal that the weak synoptic days, which are associated with highpressure systems or the ridging of highs, account for 16 − 20% of weather conditions in MarchAugust and 5% of annual rainfall over the Drakensberg. Wet weak synoptic days can induce widespread extreme rainfall (up to 20mm day−1 ) over the Drakensberg. CFSR underestimates the magnitude of the weak-synoptic-day rainfall but the WRF downscaling of the CFSR dataset enhances the quality of the simulated rainfall. All of the climate simulation datasets (WRF, MPAS, CORDEX, NEX) give realistic simulations of the precipitation indices over Southern Africa, especially over South Africa and DMR. In most cases, the biases in the simulations are within the observation uncertainties. SOM analysis reveals four major patterns of WERE patterns over the Drakensberg. The most prevalent WERE pattern usually occurs on the eastern side of the mountain, stretching from north-east to the south-west along the coastline, and it is usually induced by tropical temperate troughs, cold fronts, and the ridging highs. There is no agreement among simulations ensemble means on the annual precipitation projection over DMR. However, the ensemble means agreed on an increase in the intensity of normal precipitation and a decrease in the number of precipitation days and the number of continuous wet days. They also agreed on a future increase in frequency and intensity of extreme precipitation and widespread extreme events over DMR. SOM analysis, which elucidates the range of projection patterns that lie beneath the simulation ensemble means of the simulations, shows the most probable combination of projected changes in the annual precipitation and extreme precipitation events (intensity and frequency) over DMR: (i) an increase in both annual precipitation and extreme precipitation events; (ii) a decrease in both annual precipitation and extreme precipitation events; (iii) a decrease in annual precipitation but increase in extreme precipitation events. Results of this study can provide a basis for developing climate change adaptation and mitigating strategies over the Drakensberg.